2010
DOI: 10.1186/1471-2458-10-182
|View full text |Cite
|
Sign up to set email alerts
|

Health services utilisation disparities between English speaking and non-English speaking background Australian infants

Abstract: BackgroundTo examine the differences in health services utilisation and the associated risk factors between infants from non-English speaking background (NESB) and English speaking background (ESB) within Australia.MethodsWe analysed data from a national representative longitudinal study, the Longitudinal Study of Australian Children (LSAC) which started in 2004. We used survey logistic regression coupled with survey multiple linear regression to examine the factors associated with health services utilisation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 26 publications
1
35
1
2
Order By: Relevance
“…(Fassaert et al, 2010, Murray et al, 2010, Ou et al, 2010, Ponce et al, 2006, Poureslami et al, 2010, Puthussery et al, 2010, Sokal, 2010, Timmins, 2002) Research suggests that language barriers adversely affect patients in their access to health services (Jacobs et al, 2006, Pippins et al, 2007, Robert Wood Johnson Foundation, 2001); comprehension and adherence(Cheng et al, 2007, Jacobs et al, 2006); quality of care (Cohen et al, 2005, Diamond et al, 2009, Jacobs et al, 2003, Jacobs et al, 2006); and patient and provider satisfaction. (Arthur et al, 2014, Baker et al, 1996, Jacobs et al, 2006)…”
Section: Introductionmentioning
confidence: 99%
“…(Fassaert et al, 2010, Murray et al, 2010, Ou et al, 2010, Ponce et al, 2006, Poureslami et al, 2010, Puthussery et al, 2010, Sokal, 2010, Timmins, 2002) Research suggests that language barriers adversely affect patients in their access to health services (Jacobs et al, 2006, Pippins et al, 2007, Robert Wood Johnson Foundation, 2001); comprehension and adherence(Cheng et al, 2007, Jacobs et al, 2006); quality of care (Cohen et al, 2005, Diamond et al, 2009, Jacobs et al, 2003, Jacobs et al, 2006); and patient and provider satisfaction. (Arthur et al, 2014, Baker et al, 1996, Jacobs et al, 2006)…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study by Ou et al [3] confirmed that patients who do not speak the local language were disadvantaged in their access to health services. Language barriers also result in unequal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The Ou et al . 's study used data from the Longitudinal Study of Australian Children and was limited only to infants . Correa‐Velez et al .…”
Section: Introductionmentioning
confidence: 99%
“…6,7 To date, a limited body of literature exists describing the role of language in utilisation of healthcare particularly ED care in Australia. 8,9 Ou and colleagues found that infants from a non-English-speaking background accessed significantly less of the most frequently used healthcare services compared with infants from an English-speaking background. 8 The Ou et al's study used data from the Longitudinal Study of Australian Children and was limited only to infants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation